MiR-149-5p: An Important miRNA Regulated by Competing Endogenous RNAs in Diverse Human Cancers - Ren, Fu-jia; Yao, Yao; Cai, Xiao-yu; Cai, Yu-ting; Su, Qian; Fang, Guo-ying (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) consist of a large family of small, non-coding RNAs with the ability to result in gene silencing post-transcriptionally. With recent advances in research technology over the past several years, the physiological and pathological potentials of miRNAs have been gradually uncovered. MiR-149-5p, a conserved miRNA, was found to regulate physiological processes, such as inflammatory response, adipogenesis and cell proliferation. Notably, increasing studies indicate miR-149-5p may act as an important regulator in solid tumors, especially cancers in reproductive system and digestive system. It has been acknowledged that miR-149-5p can function as an oncogene or tumor suppressor in different cancers, which is achieved by controlling a variety of genes expression and adjusting downstream signaling pathway. Moreover, the levels of miR-149-5p are influenced by several newly discovered long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs). However, there is blank about systematic function and mechanism of miR-149-5p in human cancers. In this review, we firstly summarize the present comprehension of miR-149-5p at the molecular level, its vital role in tumor initiation and progression, as well as its potential roles in monitoring diverse reproductive and digestive malignancies.